Women in politics forms and processes - Sankaran, Kamala 1961-.; Friedrich Ebert Stiftung, New Delhi (New Delhi Har-anand Publications, 1993)
Papers presented at the round tables organized in 1990 and 1991 by various women's research and development organizations and sponsored by the Friedrich Ebert Stiftung, New Delhi.
WS-763
Keywords: Women in politics -- Congresses. -- India